2009
DOI: 10.1007/s10600-010-9479-7
|View full text |Cite
|
Sign up to set email alerts
|

Compounds from flowers of Daucus carota L. SSP. carota and their antioxidant activity

Abstract: UDC 547.972 Daucus carota L. ssp. carota, wild carrot, belongs to the family Apiaceae (Umbelliferae). It is a tall robust biennial spiny-fruited herb that grows in dried-out fields [1]. It is indigenous to Europe and has antibacterial, stumulant [2], antisteroidogenic [3], anti-flammatory [4], antiseptic, carminative, diuretic, and hepatoprotective properties [5]. Chemical studies on the seed oil and the root of Daucus carota L. have revealed a variety of chemical counstituents such as daucane-type sesquiterpe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…In this study, DCOE showed considerable radical scavenging activity when compared to that of Trolox (61% vs 90.8%). This is consistent with a previously reported antioxidant effect of dichloromethane‐methanol extract of wild carrot (Akgul et al ., ). The FRAP values obtained suggested that DCOE might act as an electron donor and might react with free radicals transforming them into more stable compounds.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In this study, DCOE showed considerable radical scavenging activity when compared to that of Trolox (61% vs 90.8%). This is consistent with a previously reported antioxidant effect of dichloromethane‐methanol extract of wild carrot (Akgul et al ., ). The FRAP values obtained suggested that DCOE might act as an electron donor and might react with free radicals transforming them into more stable compounds.…”
Section: Discussionmentioning
confidence: 97%
“…The chemical composition of the Daucus carota oil, extracted from different parts of the plant, consists mainly of phenylpropanoids, monoterpenes, sesquiterpenes and phenols in addition to polyphenols which include flavonoids (Gonny et al, 2004;Staniszewska et al, 2005;Rossi et al, 2007;Maxia et al, 2009;Wei Fu et al, 2009, 2010. A study on the dichloromethane-methanol extract of the flower of wild carrot from Turkey, using the 1,1-diphenyl-2-picryl hydrazyl (DPPH) method, revealed significant antioxidant activity (Akgul et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…This aligns with the historical utilization of wild carrots in folk medicine for the treatment different inflammatory disorders like pain, prostatitis, and cystitis [ 5 , 11 , 12 , 13 ]. The observed anti-inflammatory effect of the wild carrot may also be attributed to the existence of antioxidant compounds in the plant extract [ 24 , 37 , 66 , 67 , 108 , 109 ]. Notably, various terpenes including α-pinene, β-Caryophyllene, β-bisabolene, sabinene, limonene, and α-longipinene along with polyphenols like luteolin, kaempferol, apigenin, caffeic acid, and quercetin are recognized for their radical scavenging activities [ 110 , 111 , 112 , 113 , 114 , 118 , 119 , 121 ].…”
Section: Discussionmentioning
confidence: 99%
“…gummifer . Akgul et al [ 108 ] reported that oil extracted from D. carota L. ssp. carota flowers from Turkey possesses significant DPPH radical scavenging properties, and this effect was stronger than that of individual compounds extracted from the oil.…”
Section: Pharmacological Activitiesmentioning
confidence: 99%